2002
DOI: 10.1046/j.1464-5491.2002.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

The North‐West Diabetes Foot Care Study: incidence of, and risk factors for, new diabetic foot ulceration in a community‐based patient cohort

Abstract: More than 2% of community-based diabetic patients develop new foot ulcers each year. The neuropathy disability score, 10 g monofilament and palpation of foot pulses are recommended as screening tools in general practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

39
701
7
42

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 920 publications
(853 citation statements)
references
References 22 publications
(38 reference statements)
39
701
7
42
Order By: Relevance
“…Perspectives need to be exercised, however, as most of the reported studies on the subject in SSA are old and cross-sectional in design. However, our annual incidence is higher than that observed in developed countries, where a dramatic reduction in the rate of diabetic foot has been recorded over the past two decades [8,25,26]. The North-West and West of Ireland diabetic foot studies conducted in the United Kingdom and the Republic of Ireland reported diabetic foot incidence of 2.2% and 2.6%, respectively [8,27].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Perspectives need to be exercised, however, as most of the reported studies on the subject in SSA are old and cross-sectional in design. However, our annual incidence is higher than that observed in developed countries, where a dramatic reduction in the rate of diabetic foot has been recorded over the past two decades [8,25,26]. The North-West and West of Ireland diabetic foot studies conducted in the United Kingdom and the Republic of Ireland reported diabetic foot incidence of 2.2% and 2.6%, respectively [8,27].…”
Section: Discussionmentioning
confidence: 80%
“…However, our annual incidence is higher than that observed in developed countries, where a dramatic reduction in the rate of diabetic foot has been recorded over the past two decades [8,25,26]. The North-West and West of Ireland diabetic foot studies conducted in the United Kingdom and the Republic of Ireland reported diabetic foot incidence of 2.2% and 2.6%, respectively [8,27]. Similarly, Muller et al and de Sonnaville et al both from the Netherlands indicated an incidence of 2.1% and 1.8%, respectively [28,29].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These latter patients might therefore have had more severe disease, although in terms of ulcer stages, no differences were observed between patients who were referred by other specialists and those who were not. In addition, studies with long-term follow-up indicate that diabetic foot ulceration is a recurrent disease [34,35]. Since we excluded patients with a previous ulcer within the 12 months prior to presentation, our cohort does not properly reflect the total population attending the participating clinics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the 10 g monofilament has been found to have a similar diagnostic rate when compared to the 128 Hz tuning fork (32.6 vs 31.4%, respectively). Furthermore, the efficacy of the 10 g monofilament has been established in multiple studies [3,6]. PAD was defined as monophasic Doppler ultrasound readings, an ankle brachial pressure index (ABPI) of <0.9 or the existence of symptomatic vascular disease [4,24].…”
Section: Introductionmentioning
confidence: 99%